The Naval State in Newfoundland, 1749-1791 - Bannister, Jerry (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2000)
AbstractThis article challenges the conventional view that a colonial state did not exist in eighteenth-century Newfoundland. It rejects the traditional notion that the island's legal system was necessarily illegitimate or ineffective. It argues that despite the limited institutions allowed under statutory law and official imperial policy, an effective system of governance, based on local customs adopted under the rubric of English common law, developed to meet the needs of those in power. The Royal Navy was the engine of law and authority-in early Newfoundland. A series of major reforms undertaken in 1749 precipitated the rise of a “naval state”, which formed the basis on which local government was administered. By exploring the operation of this legal system prior to the Judicature Act of 1791, this article points to the need for historians to rethink the chronology of politico-legal development in Canada. The case of Newfoundland demonstrates that pre-industrial state formation cannot be relegated to merely an ancillary role in the dominant narrative of the rise of the “colonial leviathan” in mid-nineteenth century Canada.